“I am not an Immigrant. I am an International Student": A Qualitative Study of Adaptation Experiences of Turkish International Students in Germany - Erturk, Seda; Oker, Kemal; Nguyen Luu, Lan Anh (Journal of International Students, 2021)
This study used the consensual qualitative research method (Hill, 2015) and examined the adaptation process of 15 Turkish international students at different German universities. The results of this study yielded four primary domains of adaptation experiences: perceptions of Germany, adaptation challenges, the contributing factors in adaptation experiences, and attitudes toward counseling services. Implications for counseling practice and future directions are discussed in light of the results of this study.